Differences of Positive Linear Operators on Simplices. (25th March 2021) - Acu, Ana-Maria; Başcanbaz-Tunca, Gülen; Rasa, Ioan
Abstract : The aim of the paper is twofold: we introduce new positive linear operators acting on continuous functions defined on a simplex and then estimate differences involving them and/or other known operators. The estimates are given in terms of moduli of smoothness and K -functionals. Several applications and examples illustrate the general results.